Influência da exposição solar no perfil de metilação de DNA dos genes MMP9 e MIR137 em amostras de pele humana - Melo, Alanne Rayssa da Silva (2015)
DNA methylation is a key process for the regulation of gene expression by reversible inactivation of genes. Environmental factors such as solar radiation, can alter the DNA methylation profile. MMP-9 protein is part of a collagenases family whose function is to remodel the extracellular matrix, which presents itself very active in the early stages of cancer and photoaging. MicroRNAs are non-coding RNA molecules that act as post-transcriptional regulators of gene expression by degrading or repressing the target messenger RNA. It is estimated that about 10% of microRNA expression is controlled via DNA methylation. The microRNA-137 has tumor suppressor function in various types of cancer, including squamous cell carcinoma and melanoma. The aim of our study was to analyze the influence of sun exposure on the DNA methylation profile of matrix metalloprotease-9 (MMP9) and microRNA-137 (MIR137) genes of skin cells. To this purpose, skin samples were analyzed, which were obtained from sun-exposed and sun-protected areas from 28 corpses of both sexes, aged 30-89 years with no history of skin diseases obtained from the Brazilian Service of Death Investigation. Genomic DNA was extracted using Trizol and with the aid of a tissue homogenizer. The DNA methylation analysis was performed using Methylation Specific PCR (MSP) by previous modification of the DNA with sodium bisulfite. The amplified samples were subjected to electrophoresis on polyacrylamide gel followed by staining with silver nitrate. Statistical analysis was performed using the McNemar paired test at a significance level of 5%. No differences were found among the areas (p>0.05), with the partially methylated condition found to be a common event in skin for both MMP9 (96.4% of samples) and MIR137 (60.4% of samples). We conclude that sun exposure does not induce changes in DNA methylation status in the studied CpG sites.